Fine motor and self‐care milestones for individuals with Down syndrome using a Retrospective Chart Review. (23rd December 2014) - Frank, K.; Esbensen, A. J.
Abstract Background Developmental milestone markers for fine motor and self‐care skills among children with Down syndrome (DS) are either minimal, anecdotal or out‐of date. Our goal was to produce normative expectations for the development of fine motor and self‐care milestones specific to children with DS. Method A cross‐sectional retrospective chart review was completed on 274 children with DS seen at a specialty clinic that ranged in age from 4 months to 18 years. Specific skills were assessed at occupational therapy assessments as either present or absent, including fine motor, handwriting, scissor usage, self‐feeding and clothing management. Results Fine motor milestones describing when 10–30% ('early achievers') and 75–95% ('representative achievement') of children with DS had mastered each skill were developed based upon descriptive review. As the fine motor and self‐care skills advanced in complexity, the range of ages for documented skill acquisition was observed to increase. Conclusions Age ranges for the mastery of fine motor developmental milestones for early and representative achievement were developed based upon descriptive analysis of cross‐sectional retrospective clinical chart reviews. That the age range for mastering fine motor and self‐care skills broadens as children with DS get older is in agreement with what is identified in the DS behavioural phenotype with regard to variable motor skills overall. These fine motor and self‐care developmental milestone markers contribute to the field by informing parents, caregivers and healthcare providers of potential fine motor and self‐care outcomes and describing normative development for children with DS.